The Effect of Metanolic Extract and Ethyl Acetate Fraction of Kepel Fruits to Lipid Peroxide Concentration in Liver of CCl4-induced Rat - Mitsalina Fildzah Arifah; Sudibyo Martono; Sugeng Riyanto; Claude Mona Airin (LPPT Universitas Gadjah Mada, 2019)
Accumulation lipid peroxidation can lead to the formation of malondialdehyde to generate free radicals. Antioxidant will minimize free radical related health problems, such as natural antioxidant from meat of kepel (Stelechocarpus burahol) (Blume) Hook. F. & Thompson) fruits. Antioxidant activities of methanol extracts and acetate ethyl fractions meat of kepel fruits calculated profile of malondialdehyde concentration (ng/mL) in CCl4 induced acute liver toxicity in female Sprague Dawley rats using ELISA competitively method. All of groups induced CCl4 i.p. at 0 h, except untreated and solvent control group, then vitamin C , methanol extracts and acetate ethyl fractions p.o. once daily for 72 h. Identification of secondary metabolite was using phytochemical screening and Thin Layer Chromatography (TLC). Liver weighed and calculated relative organ weight (ROW) of liver, then all of data analyzed using statistic tests, One Way ANOVA and Kruskall Wallis. This study showed methanol extracts can decrease MDA concentration, ALT and AST were more potent (significantly p<0.05) than acetate ethyl fractions and vitamin C. The TLC analysis identified methanol extracts have same polarity with quercetin (Rf = 0,26) and acetate ethyl fractions showed other flavonoid class, except rutin and quercetin. ROW of acute liver toxicity in rats increased significantly in CCl4 and vitamin C groups.